TEOLOGI SOSIAL MUSLIM TIONGHOA: KEIMANAN, IDENTITAS KULTURAL DAN PROBLEM EKSISTENSIAL - Achmad Muhibin Zuhri; Winarto Eka Wahyudi (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2020)
Chinese Muslims have a cultural identity as a double minority. In Islam, they are a minority within their ethnic religion and remain a minority among other ethnic groups in Indonesia. This ethnic group embraces Islam mostly because of religious conversion. The aspect of religious conversion makes ethnic Chinese come to Islam. This study aims to find the expression of Muslim in Surabaya, who are using social action tools asa manifestation of their faith to gain trust from the mainstream while maintaining their cultural identity as Chinese so as not to experience alienation in their communities. This study found that Chinese Muslim’s social theology in Surabaya serves as an articulation of cosmopolitan Islam that is successfully integrated into an inclusive Chinese identity. This also confirms that being a good Muslim is not in a binary position with being a pure Chinese. Besides, the theological vision of Chinese Muslims is expressed not only by maintaining its cultural background, but also through social movements that are inspired and based on Islamic dogmatic teachings that emphasize human values.Keywords: Social Theology, Chinese Muslims, Existential Problems